The archaeology of Prague and the medieval Czech lands, 1100-1600 - Klápště, Jan 1949- (Equinox, 2016)
"This book offers the first comprehensive picture of medieval archaeology of the Czech Lands available in English. As it assembles the main topics of current archaeological research, it establishes the key issues of its methodology. The topics cover the rural and urban milieu, secular power supports (castles, manors etc.), and monastic houses and parish churches. Special attention is given to technology, craft, industry (including mining archaeology and glass production), housing culture and daily life across the social strata. One of the fascinating features is the artefactual presentation of two competing religions; Catholicism and Hussitism. Czech medieval archaeology reveals new details of Jewish everyday life, and the story of the Anabaptists and their Central European crafts heritage. The achievements of contemporary Czech medieval archaeology are well documented while the text ventures on an archaeological journey through the medieval Czech Kingdom: from Prague up to its forgotten rural environment. The primary intention is to piece together the past and illustrate the position of the Czech Lands between the gradual process of medieval transformation (13th century) and early modern transition (16th century). The nine thematic chapters of this work contain an array of boxed texts by specialized researchers, highlighting the themes of particular importance. The entire book is illustrated by figures which have been until now practically unknown in the European context"...Provided by publisher
Includes bibliographical references and index
Keywords: Geschichte 1100-1600; Geschichte; Funde; Archaeology, Medieval -- Czech Republic -- Prague; Archaeology, Medieval -- Czech Republic; Excavations (Archaeology) -- Czech Republic -- Prague; Excavations (Archaeology) -- Czech Republic; Social archaeology -- Czech Republic; Social archaeology -- Czech Republic -- Prague; Social change -- Czech Republic -- History; Social change -- Czech Republic -- Prague -- History; Archäologie; Tschechische Republik; Prague (Czech Republic) -- Antiquities; Czech Republic -- Antiquities; Tschechien